Onshore Pipeline Design Using GRP Pipe Material - Hutagaol, Paris
In oil and gas industries, steel pipes are mostly applied for pipeline. However there is a fundamental problem at the usage of steel pipes which is low resistance of steel pipes to corrosion, especially at a pipeline in which the corrosive fluid is transmitted while it passes an aggressive area. To solve this problem, one of the alternatives is by using pipe made from corrosive resistant material, such as Glass Reinforced Plastics (GRP) composite pipe. This final project studied the pipeline design using GRP composite pipe. It includes selection of pipe wall thickness, static span analysis, burial analysis, stress analysis, flexibility analysis, global buckling analysis, and electrostatic analysis of GRP pipes system. All analysis based on Standard ISO 14692:2002. The case study is at the pipelines at Pondok Tengah oil and gas field. This pipelines connect all clusters and processing units for well fluid, gas and crude transmission. From the analysis result, considering all design aspect, it is obtained that the pipe product selected by Star FRP Series 1500-ACT (API 15HR Design) NPS 8", 6”, 4” for well fluid and gas transmission and Star FRP Series 800-ACT ( API 15HR Design) NPS 8” for crude transmission is safe to be applied for the installation, operation and hydrotest condition.